The new deal - Case, Jonathan (Dark Horse Books, 2015)
"The Waldorf Astoria is the classiest hotel along the Manhattan skyline in 1930s New York City. When a charming woman checks in with a high-society entourage, a bellhop and a maid get caught up in a series of mysterious thefts. The stakes quickly grow perilous, and the pair must rely on each other to discover the truth while navigating delicate class politics" --